The Effect of Changes in Profitability, Revenue Growth, Leverage and Company Size on Tax Avoidance (Empirical Study of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2020-2023) - Dharma Priatmaja, Ade; Triyono (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
Tax avoidance is a step taken by companies to suppress taxable income through strategies that are legally or unlawfully prepared. This study is intended to understand and evaluate the impact of profitability, revenue growth, leverage, and company size regarding tax avoidance practices on food and beverage business entities listed on the Indonesia Stock Exchange during the 2020-2023 period. This study involved 45 business entities selected by utilizing the purposive sampling method. The research findings reveal that profitability, leverage, and company size partially contribute positively and significantly to tax avoidance. Meanwhile, revenue growth has no impact on tax avoidance.